Endoscopic ultrasound-guided creation of an enterocolostomy to relieve malignant bowel obstruction - Mir, Adil; Parekh, Parth J.; Shakhatreh, Mohammad; Yeaton, Paul (Endoscopy International Open, 2019)
Background and study aim Malignant bowel obstruction can cause significantly distressing symptoms in patients with end stage cancers, often requiring invasive surgical intervention. With such procedures, risks often outweigh the benefit. We report a novel application of the AXIOS stent and electrocautery-enhanced delivery system to create an enterocolostomy to bypass a small bowel obstruction in the setting of recurrent malignant bowel obstruction. A 72-year-old patient presented with recurrent malignant bowel obstruction and was deemed unfit for surgery. Endoscopic ultrasound was used to deploy an AXIOS stent, creating an enterocolostomy resolving the obstruction.